ABSOLUTE AND RELATIVE BIOAVAILABILITY STUDY FOR THE NEWLY DEVELOPED NASAL NANOEMULSION IN SITU GEL OF ONDANSETRON HCl IN COMPARISON TO CONVENTIONALLY PREPARED IN SITU GEL AND INTRAVENOUS DOSAGES FORMS - Maraie, Nidhal K.; Almajidi, Yasser Q.; Alshadher, Ahmed (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of the work was to study the absolute and relative bioavailability (using rabbits) of ondansetron HCl (ONH)from our newly prepared intranasal mucoadhesive nanoemulsion in situ gel (NIG) in comparison to intranasal mucoadhesive in situ gel (IG) prepared by the conventional method and intravenous injection. Methods: Six male rabbits weighing 2.5-3 kg were used in this study, where the dose of ondansetron HCl (ONH) was calculated based on the body surface area (BSA) which is equivalent to 140μl (containing 10 mg/ml) of NIG and IG and 700μl of intravenous Zofran® injection (containing 2 mg/ml) were given to the rabbits, separated with one week washout period. Serial blood samples were withdrawn and analyzed for simultaneous determination of the drug using HPLC (Knaure; 150 ×4.6 mm; 5 μm particle size; 25 cm length) supported by guard column C18-4 mm diameter. Results: The pharmacokinetics parameters for NIG; Cmax, Tmax, AUC0-t, AUC0-∞were found to be greater than conventional in situ gel (IG). In vivo pharmacokinetic studies in rabbits showed a significant increase in Cmax and AUC 0-α(P<0.001) with shorter Tmaxusing NIG compared to IG containing the same NIG excipients, while the absolute bioavailability for NIG and IG (was 80.541 and 51.068 respectively). Conclusion: The present studies ratify the bioavailability enhancement potential of NE used to prepare NIG for the drug and significantly high absolute bioavailability to be used as a successful alternative route to the IV injection and improve patient compliance.